Pengaruh Karakteristik Perusahaan Terhadap Lamanya Waktu Penyelesaian Audit (Audit Delay) Pada Sub Sektor Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI - Siti Fatimah; Dirvi Surya Abbas (LPPM Universitas Putera Batam, 2022)
Audit delay or the completion of the audit period may affect the timeliness of the information published and can affect the level of uncertainty that decision based on published information. Characteristic of the company is one of the factors that affect audit delay. This research aimed to examine the influence of the characteristics of the company, which consists of company size, solvency, profit or loss company on audit delay in the manufacturing companies listed on the Indonesia Stock Exchange (IDX) by adding one variable that is thought to have an influence on audit delay, i.e. the size of Public Accounting Firms. The entire manufacturing companies listed on the IDX in 2007 to 2010 are population in this study. Purposive sampling technique is used to obtain the sample size by 69 manufacturing companies with the acquisition of observational data as much as 276. Multiple regression analysis is used to test hypotheses to explain the relationship between the variables in this research. The results of the partial examination showed that all independent variables are characteristics of the company consists of company size, solvency, profit or loss of the company, and the size of the Public Accounting Firms has a significan influence on audit delay